Computer Mediated Communication and Vocabulary Learning: The Case of Facebook - Ghaouar Nesrine; Laiche Sara; Sabah Belhadi (Universitas Cokroaminoto Palopo, 2019)
Nowadays, Computer-Mediated Communication (CMC) becomes the most dominant mode of communication as computers, smart phones, tablets are worldwide used devices for communication especially with the internet facilities through different platforms. However, despite the spread of computer mediated communication modes and devices, it is noticed that people still lack vocabulary in the English language. Therefore, this research intends to investigate Facebook use as a shared online space to learn vocabulary in English language. In addition, it aims at developing, within Facebook users, the possible vocabulary learning strategies that would enhance their English vocabulary learning. Therefore, two research tools were used with a group of facebook users: a questionnaire and an experiment. The obtained results confirmed that the participants under investigation have significantly improved their vocabulary learning via Facebook. In addition, vocabulary learning has been greatly affected by certain training on some strategies. Hence, Facebook proved to be not only a source of entertainment, but also an effective informal learning tool of English vocabulary.